Daring to compete : how 7 drivers of growth accelerate entrepreneurs to market leadership - Foreman, Diane, 1960-; Pearce , Bryan, 1959-; Godding , Geoffrey, 1959- (Hoboken : Wiley, 2019)
The successful entrepreneur's guide to accelerating growth Daring to Compete offers real-world strategies to accelerate the growth of your business and secure your place as a market leader. This expert guide is the result of years of comprehensive research and experience from global professional services organization EY, originator of the celebrated "Entrepreneur Of The Year" program. Employing its worldwide reach and extensive network of successful entrepreneurs, EY has developed a model of sustainable business development--"The 7 Drivers of GrowthTM." This innovative and highly effective approach to strategic growth is an invaluable resource for high-growth businesses, entrepreneurs, and start-ups. Favoring practical strategies over abstract theories, this book provides clear guidance on the Customer; Funding and Finance; Transactions and Alliances; Risk; People, Behaviors, and Culture; Digital Technology and Analytics; and Operations. This book brings the application of these drivers to life by featuring insights from Entrepreneur Of The Year award-winning entrepreneurs from a wide range of industries and geographic locations. These entrepreneurs share how each driver functions in actual business situations and present first-hand advice on their application and implementation. Planned and sustainable growth is a challenge faced by businesses every day, from developing ventures to leading enterprises. Effective entrepreneurs embrace the drivers of growth and recognize what areas require sharper focus. This book allows you to identify and apply these elements in your own business--facilitating optimal outcomes and accelerating growth. This indispensable guide enables you to: Implement a proven business model to compete more effectively and achieve market leadership Gain the knowledge and confidence to face challenges, anticipate, and overcome obstacles Access research, tools, and services to accelerate growth and compete on a global scale Learn invaluable market leadership strategies from a team of highly successful entrepreneurs Developed from the real-life stories of EY Entrepreneur Of The Year winners, this book is an inspirational and informative must-read guide to business growth and market leadership. Daring to Compete is an invaluable resourcefor both aspiring and experienced entrepreneurs and established business leaders seeking to become more entrepreneurial.
When do I want the relationship to begin and how long should it continue?Who will be responsible on both sides for managing the relationship?; Transaction effectiveness; Maximizing transaction value; Structuring the transaction; Valuing the target; Due diligence, deal negotiation, and structuring; Integrating the business and extracting intended value; Chapter 13. Driver #7: Risk "Threat or opportunity"; Creating value from risk management; Stakeholder management; Policies, procedures, and compliance; Governance; EY 7 Drivers of Growth: many success stories
Keywords: Entrepreneurship; Leadership; Entrepreneurship; Leadership; Entrepreneuriat; Leadership; entrepreneurs; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Entrepreneurship; Entrepreneurship; Leadership